2015
DOI: 10.1017/aee.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Opinions on Animal Culling: A South Australian Example

Abstract: Environmental education is commonly used to satisfy the natural curiosity of tourists, increase conservation awareness and strengthen proconservation values. Yet it does not always address the more sensitive ecosystem management issues such as animal culling as it may be seen to upset the balance of the positive tourist experience. For this reason, this study compared acceptance and non-acceptance of animal culling from two angles: for tourists either provided or not provided with a brief passage of informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“… prior modelling of climate change impacts and adaptation options for biodiversity (Prober et al 2012, Williams et al 2014, Prober et al 2015a) and agriculture (e.g. , 2015, 2014, Potgieter et al 2013, Yang et al 2014, Anwar et al 2015 in the region;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… prior modelling of climate change impacts and adaptation options for biodiversity (Prober et al 2012, Williams et al 2014, Prober et al 2015a) and agriculture (e.g. , 2015, 2014, Potgieter et al 2013, Yang et al 2014, Anwar et al 2015 in the region;…”
Section: Methodsmentioning
confidence: 99%
“…Five sets of constraints were led by values (in the sense of Schwartz, 2012;O'Brien and Wolf, 2010), and these appeared the most difficult to overcome (Table 3). For example, views on culling native animals can involve deep-set ethical beliefs, that education may only partly modify (Mowska, 2015). Similarly, trade-offs between production and biodiversity benefits lead to conflicting interests and views regarding introduction of exotic plants, and this conflict remains unresolved in other Australian ecosystems (Driscoll et al, 2014).…”
Section: Perspectives On Application Of the Values-rules-knowledge Frmentioning
confidence: 99%
“…Other beliefs, such as perceived nativeness, were less influential. Moskwa [ 36 ] found that tourists did not show significant differences in their opinion regarding culling non-native and native species and only changed their opinion when given information regarding why animals may be culled. Nates et al [ 37 ] found that young Argentinean rural student’s preferences and perceptions were strongly directed towards 18 non-native domestic species.…”
Section: Discussionmentioning
confidence: 99%